Jesse Shera, The Wars and The Pietá: social epistemology as criticism of information ontology - Bozzetti, Rodrigo Porto; Saldanha, Gustavo (Faculdade de Filosofia e Ciências, 2017)
The purpose of this paper, considering the relevance of Shera thoughts and its repercussions, is to reposition, in epistemological-historical terms, Jesse Shera’s approaches and their impacts according to a relation between life and work of the epistemologist. Without the intention of an exhaustive discussion, the purpose is to understand some unequivocal relations between the Shera critique for the context of its theoretical formulation and the consequences of this approach contrary to some tendencies originating from the technical and bureaucratic roots of the field (before and after World War II). It is deduced that Shera, rather than observing the sociopolitical reality and technical partner in which the texture of alibrary-based thought (but visualized by him as documentaryinformational), establishes, in his own praxis, social epistemology as a sort of "critique of the future," that is, as a praxis of the reflexive activity of the subject inserted in this episteme. In our discussion, the epistemological-social approach represents a vanguard for the context of its affirmation, a reassessment for the immediate decades to its presentation(years 1960 and 1970) and a critique for the future of what was consolidated under the notion of information Science, anticipating affirmations of "social nature" of the 1980s and 1990s in the field of information.